1959
DOI: 10.1346/ccmn.1959.0080115
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Synhesis of Hectorite

Abstract: Hectorite, a trioctahedral magnesium montmorillonite, has been synthesized a t atmospheric pressure and reflux temperature. The reaction mixture was the system SiOz/MgO/LizO (or L3)/NazO in a large excess of water. The starting ratios were based on the following formula for the mineral [(LizMg~-z)SisOso(OH)4]z-.xNa+.Li+ has been found to accelerate the crystallization, and reasons for this effect are considered. Lowering of the p H of the reaction mixture by the use of alkali metal fluorides rather than hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1977
1977
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 3 publications
0
10
1
Order By: Relevance
“…Moreover, in such a case, the presence of Cu(II) triggers the formation of Mg-F richterite. Since this phase can also be a conversion product of hectorite in the absence of Cu(II), but with a concentration of F which is five times greater than in the present experiment http://doc.rero.ch (Granquist and Pollack, 1959), Cu(II) probably influences either the distribution or the thermal stability of F in the sample. In the first case the simultaneous enrichment of Cu(II) and F would lead to broadening of the Cu(II) EPR signal due to dipole-dipole interactions, which was not observed.…”
Section: Thermal Conversioncontrasting
confidence: 61%
“…Moreover, in such a case, the presence of Cu(II) triggers the formation of Mg-F richterite. Since this phase can also be a conversion product of hectorite in the absence of Cu(II), but with a concentration of F which is five times greater than in the present experiment http://doc.rero.ch (Granquist and Pollack, 1959), Cu(II) probably influences either the distribution or the thermal stability of F in the sample. In the first case the simultaneous enrichment of Cu(II) and F would lead to broadening of the Cu(II) EPR signal due to dipole-dipole interactions, which was not observed.…”
Section: Thermal Conversioncontrasting
confidence: 61%
“…The resulting silicometallic precipitate contained small smectite nuclei, the crystallinity of which improved upon aging in the aqueous suspension at temperatures below 100~ In contrast to the method of Harder (1972Harder ( , 1977, this procedure allows better control of the homogeneity of the smectites, is easily reproducible, and can produce large quantities of material. Granquist and Pollack (1960) synthesized hectorite by hydrothermal treatment of an aqueous slurry containing -10% freshly precipitated Mg(OH)2, silica gel, and various amounts of NaOH, LiOH, and LiE The synthesis conditions used ranged from reflux temperature and atmospheric pressure to 300~ and --83 bars. Use of LiF accelerated the crystallization of hectorite.…”
Section: Clays and Clay Mineralsmentioning
confidence: 99%
“…ence may have been due to the high degree of crystallinity of Li-bearing smectite or to the lack ofoctahedral fluorine (see Granquist and Pollack, 1960). The differential thermal analysis curve of hectorite from Hector, California, had a low-temperature peak at 118 ~ 128~ and a dehydroxylation endotherm at 670~ Mackenzie (1957) and Deer et al (1962) reported a dehydroxylation temperature of 800~ for this hectorite.…”
Section: Clays and Clay Mineralsmentioning
confidence: 92%